Calls for police service: Understanding the demand profile and the UK police response. (March 2017) - Boulton, Laura; McManus, Michelle; Metcalfe, Lauren; Brian, David; Dawson, Ian
In times of austerity and police budget cuts, it is important to understand the demand on the UK police service in order to reduce it effectively. This paper reviews the demand on a division within a police service in England over the period of a year. Utilising police data records, it combined descriptive statistics with content analysis to identify areas of demand. Findings revealed that the majority of the Constabulary's resources were spent addressing non-traditional police demand. Results indicate that the police could potentially reduce demand for service by enhancing work within two key areas: partnership working and early intervention.